Improving the Work Breakdown Structure of the Plant Installation - Case: Asphalt Plant - Abujudeh, Said (International Journal of Engineering and Management Sciences, 2018)
The improvement of the project management forced the industrial organizations to focus on using the project management techniques in their industry, to plan and control the workflow to achieve their targets, further to increase the satisfaction of their customers. One of the most common project management tools are used is the work breakdown structure (WBS), which provide a framework for the implementation of the project scope including project planning, scheduling, monitoring, control, and estimation. Depending on the top-down approach the project activities will be broken into smaller parts that can be measured and controlled during the project implementation. The well-defined construction of the structure contributes to making the project more realistic and visual. However, the misunderstanding of the project WBS among the project team creates deflection and misinterpretation of the project scope. The main issue of this research is to improve the WBS of the installation plan and develop a standard WBS for plant installation. The research was limited to Asphalt plant installation WBS as a case study to identify the weaknesses of the current WBS at the case company which leads to extra installation time and cost. The research is offering a template WBS based on the company logic, defining the frequent risks that affect the plant installation based on the WBS and suggesting a suitable response strategy by recommending a control framework to monitor and control the WBS schedule throughout all installation phases.